(untitled) (AACINI - International Journal of Industrial Engineering, 2023)
Entrepreneurship is a topic of interest, increasingly relevant for societies, given its economic, productive, and cultural impact. The objective of the study was to analyze the elements that influence the decision of university students to start a business. A qualitative and non-probabilistic research was carried out through 15 semi-structured interviews with university entrepreneurs on the campus of a higher education institution in central Mexico. The findings suggest that the elements that influence the decision to start a business among university students are the search for entrepreneurial success, the different types of motivators and the obtaining-increase of income. This converges with the existing literature on entrepreneurship, but at the same time provides a new approach to entrepreneurship in university students. Suggestive findings are the divergent perception of the role of innovation in university entrepreneurship, the strengthening of the sense of community (social support), communication-persuasion and the use of social networks among university entrepreneurs. These results allow strengthening the construct, but also show the importance of entrepreneurship from within universities. Areas of opportunity for future research as well as limitations are discussed.